Annular laser cladding of CuPb10Sn10 copper alloy for high-quality anti-friction coating on 42CrMo steel surface. (February 2023) - Wan, Le; Cheng, Mengyin; Fu, Geyan; Wei, Chao; Shi, Tuo; Shi, Shihong
Highlights: A novel annular laser cladding (ALC) method for preparing low-absorptivity copper alloy materials coatings was proposed. The energy absorption model of the ALC was established and an anti-friction coating of CuPb10Sn10 was realized. The optimized ALC parameters effectively increased the laser absorptivity by 58%. The ALC coating of CuPb10Sn10 have a reliable microstructure. The ALC process was shown to be sufficient to prepare copper alloy coatings on carbon steel. Abstract: Reducing the damage caused by friction and wear to components such as Al alloy parts could extend the service lives of parts in automobile and other industrial fields. An effective approach to this is improving the anti-friction properties of key surfaces. In this study, an annular laser cladding (ALC) method was designed, an energy absorption model of the ALC process was established, and the cladding of a CuPb10Sn10 copper alloy coating on a 42CrMo steel surface was studied experimentally. The effects of the ALC process parameters on the laser absorptivity, porosity, and microstructure of the ALC sample were analyzed, and the coating properties (e.g., microhardness and anti-friction properties) were evaluated. The results showed that laser cladding of a CuPb10Sn10 copper alloy coating or other coating materials with low absorptivity could be realized on the surface of 42CrMo steel using the ALC process. The ALC process increased the laser absorptivity to 58 %, and the porosity of the ALC sample was reduced to 0.39 %. The coating microstructure was divided into three layers, in which the top layer of the Cu-rich phase had a uniform structure and no macroscopic crack defects. The main anti-friction component Pb phase and other Cu, Pb, and Sn elements were uniformly distributed. The microhardness of the coating fluctuated, and the value of the top-layer Cu-rich phase was approximately 120 HV0.3 . The shear strength of the coating was 194 MPa, and the friction coefficient of the coating decreased by approximately 50 % to 0.19. The ALC method effectively improved the laser absorptivity during the laser cladding of copper alloys on iron substrates, providing theoretical guidance for designing and manufacturing anti-friction functional components in the automotive industry and other fields.